Do Adult Spinal Deformity Patients Undergoing Surgery Continue to Improve From 1-Year to 2-Years Postoperative?. Issue 4 (May 2023) - Zuckerman, Scott L.; Lai, Christopher S.; Shen, Yong; Cerpa, Meghan; Lee, Nathan J.; Kerolus, Mena G.; Ha, Alex S.; Buchanan, Ian A.; Devin, Clinton J.; Lehman, Ronald A.; Lenke, Lawrence G.
Objective: Evaluate clinical improvement as measured by patient-reported outcomes (PROs) during the 1 to 2-year interval. Study Design: Retrospective Cohort. Methods: A single-institution registry of ASD patients undergoing surgery was queried for patients with ≥6 level fusions. Demographics and radiographic variables were collected. PROs collected were the ODI and SRS-22r scores at: preoperative, 1-year and 2-years. Outcome measures of clinical improvement during the 1-2 year time interval were: 1) group medians, 2) percent minimum clinically important difference (MCID), and 3) percent minimal symptom scale (MSS)(ODI < 20 or SRS-pain + function >8). Wilcoxon rank-sum tests, chi-squared tests, Kruskal-Wallis tests, and logistic regression were performed. Results: 157 patients undergoing ASD surgery with minimum of 1-year follow-up were included. Mean age was 53.2 and mean instrumented levels was 13.1. Preoperative alignment was: Neutral Alignment (NA) 49%, Coronal Malalignment (CM) 17%, Sagittal Malalignment (SM 17%), and Combined Coronal/Sagittal Malalignment (CCSM) 18%. Preoperative to 1-year, and preoperative to 2-years, all ODI/SRS-22r significantly improved ( P < .001).In all patients, the only significant improvement in PROs between 1-and 2-year postoperative were those reaching ODI MCID (69% 1-year vs. 84% 2-years; P < .001).Subgroup analysis: ≥55 years had an improved median ODI (18 vs. 8; P = .047) and an improved percent achieving ODI MCID (73% vs. 84%, P = .048). CCSM patients experienced significant improvement in SRS-appearance score (75% vs. 100%; P = .050), along with those with severe preoperative SM >7.5 cm (73% vs. 100%; P = .032). Conclusions: Most ASD patients experience the majority of PRO improvement by 1-year postoperative. However, subsets of patients that may continue to improve up to 2-years postoperative include patients ≥55 years, combined coronal/sagittal malalignment, and those with severe sagittal malalignment ≥7.5 cm.